Mauritania : Effective Ownership of the Poverty Reduction Strategy Paper (PRSP) Process - Lemrabott, Mohamed; Rahman Khan, Aisha (World Bank, Washington, DC, 2012)
The Mauritanian PRSP focuses on poverty reduction, strong country ownership, and the active participation of civil society. The PRSP reflects many of the recommendations of civil society. Nongovernmental organizations commented mainly on issues related to governance, education, and health and nutrition. The alliances and partnerships forged through the PRSP process have laid the groundwork for a country-driven, operationally focuses PRSP.